Analysis of Determinants Influencing Transfer Pricing - Herma Wiharno; Lia Dwi Martika; Amir Hamzah; Tia Septiani (Universitas Yudharta Pasuruan, 2023)
English VersionThis research aims to analyze the influence of taxes, bonus mechanisms, tunneling incentives, and firm size on the decision to engage in transfer pricing by mining companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. The method used in this research is descriptive and verificative with quantitative data. The population of this research is mining companies listed on the IDX from 2018 to 2020, consisting of 47 companies with a sample size of 35 companies. The data collection technique used in this research is nonpartisan observation using logistic regression analysis. Taxes, bonus mechanisms, tunneling incentives, and firm size have a significant simultaneous effect on the decision to engage in transfer pricing. Taxes have a significant positive effect on the decision to engage in transfer pricing. Bonus mechanisms have a significant positive effect on the decision to engage in transfer pricing. Tunneling incentives have a significant positive effect on the decision to engage in transfer pricing. Firm size has a significant positive effect on the decision to engage in transfer pricing. Versi IndonesiaPenelitian ini bertujuan mnguji peran pajak, mekanisme bonus, insentif tunneling, dan ukuran perusahaan terhadap pilihan melakukan transfer pricing pada perusahaan pertambangan di Bursa Efek Indonesia (BEI) 2018-2020. Penelitian ini tergolong penelitian deskriptif dan metodologi verifikasi dengan data kuantitatif. Adapun populasi penelitian berjumlah 47 sedangkan sampel ppenelitian berjumlah 35 perusahaan. Metode pengumpulan data yang digunakan adalah observasi non-partisan melalui analisis regresi logistik. Pajak, mekanisme bonus, insentif tunneling, dan ukuran perusahaan berpengaruh secara simultan pada transfer pricing. Selanjutnya hasil pengaruh parsial antaralain; Pajak, Mekanisme bonus dan ukuran perusahaan mempunyai pengaruh positif yang signifikan terhadap keputusan melakukan transfer pricing. Insentif tunneling mempunyai dampak positif yang signifikan pada transfer pricing